2019
DOI: 10.3389/fonc.2019.00869
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Cancer Radioresistance

Abstract: Radiation is a mainstay of cancer therapy. Radioresistance is a significant challenge in the treatment of locally advanced, recurrent and metastatic cancers. The mechanisms of radioresistance are complicated and still not completely understood. Exosomes are 40–150 nm vesicles released by cancer cells that contain pathogenic components, such as proteins, mRNAs, DNA fragments, non-coding RNAs, and lipids. Exosomes play a critical role in cancer progression, including cell-cell communication, tumor-stromal intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 70 publications
0
57
0
Order By: Relevance
“…While cancer therapies adversely impact cognition, they also affect exosome biogenesis and release causing changes to the anatomy of the brain [104]. Cancer therapies also cause cellular stress that affect the release and composition of exosomes, thereby impacting neighboring and distant cells (e.g., brain) [108]. Moreover, radio-and chemotherapy may also influence the development of treatment-resistant cancer cells [75], possibly through cellular reprogramming [109] and/or the formation of brain metastasis [110].…”
Section: Mechanisms Associated With Exosomes and Crcimentioning
confidence: 99%
“…While cancer therapies adversely impact cognition, they also affect exosome biogenesis and release causing changes to the anatomy of the brain [104]. Cancer therapies also cause cellular stress that affect the release and composition of exosomes, thereby impacting neighboring and distant cells (e.g., brain) [108]. Moreover, radio-and chemotherapy may also influence the development of treatment-resistant cancer cells [75], possibly through cellular reprogramming [109] and/or the formation of brain metastasis [110].…”
Section: Mechanisms Associated With Exosomes and Crcimentioning
confidence: 99%
“…Studies have shown that exosomes are closely related to tumor radiotherapy resistance. 22 The proteome content of exosome is affected by radiation in head-and-neck cancer cells. In turn, exosomes are able to modify the radiation response.…”
Section: Discussionmentioning
confidence: 99%
“…Gain‐functional and loss‐functional experiments revealed that overexpression of circMYC could promote cell proliferation and reduce radiosensitivity, while knockdown of circMYC‐inhibited cell proliferation and enhanced radiotherapy effect. Studies have shown that exosomes are closely related to tumor radiotherapy resistance 22 . The proteome content of exosome is affected by radiation in head‐and‐neck cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Xu and co-workers have reported that X-ray irradiation increase exosomes biogenesis and secretion (46). In addition, several laboratories demonstrated that EVs from irradiated tumor cells promoted genomic instability and resistance in non-irradiated cell (47,48). In summary, through investigating irradiated MCF-7 cells with the different doses of electron beam affecting the viability, apoptosis, EVs release, expression of genes involved in apoptosis and stemness, and migration capacity, we shed light into cellular responses of MCF-7 against EBI (Fig.…”
Section: Discussionmentioning
confidence: 99%